Rhynchophylline Regulates Calcium Homeostasis by Antagonizing Ryanodine Receptor 2 Phosphorylation to Improve Diabetic Cardiomyopathy - Liu, Jiao; Zhao, Yating; Zhu, Yufang; Wang, Yan; Liu, Xiaoshuang; Nie, Xiaobo; Zhao, Jing; Wang, Wei; Cheng, Jie (Frontiers in Pharmacology, 2022)
Diabetic cardiomyopathy (DCM) is a serious complication of diabetes that can lead to heart failure and death, for which there is no effective treatment. Rhynchophylline (Rhy) is the main effective component of the Chinese herbal medicines uncaria rhynchophylla, which mainly acts on the cardiovascular and nervous systems. However, its role in protecting against DCM remains unexplored. The present study aimed to explore the mechanism of Rhy in improving type 2 diabetes mellitus (T2DM) myocardial lesions from the perspective of regulating calcium homeostasis in cardiomyocytes. We prepared mice model of T2DM using high-fat diet combined with low doses of streptozotocin(STZ). The T2DM mice were given 40 mg/kg Rhy for 8 weeks. The results show that Rhy can attenuate cardiac pathological changes, slow down heart rate, decrease serum cardiac enzyme levels, reduce cardiomyocyte apoptosis, enhance cardiomyocyte contractility, increase calcium transient amplitude in T2DM mice. Further, Rhy down-regulated the phosphorylation level of ryanodine receptor (RyR)2, up-regulated the phosphorylation level of phospholamban (PLB), protected mitochondrial structure and function and increased ATP levels in cardiac tissue of T2DM mice. Our results demonstrate that Rhy can protect against myocardial damage in T2DM mice and promote cardiomyocyte contraction, and its mechanism of action seems to be related to the regulation of intracellular calcium homeostasis.